(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article explores the role of the STEAM approach (Science, Technology, Engineering, Arts, Mathematics) in developing critical thinking skills among students. Critical thinking is expressed as a person’s ability to conduct logical analysis, evaluate evidence, make decisions, and justify their opinions. The article examines the theoretical foundations of STEAM education, its pedagogical advantages, mechanisms for fostering critical thinking through interdisciplinary integration, as well as the experience of implementing this approach in Uzbekistan’s education system. Furthermore, it highlights international experiences, the scientific perspectives of Uzbek researchers, and practical recommendations emphasizing the role of the STEAM methodology in promoting critical thinking.